Ethnobotany of Lontar (Borassus flabellifer L.) in Tuamese Village, East Nusa Tenggara - Ite Morina Yostianti Tnunay; Dicky Frengky Hanas (Jurnal Ilmu Pertanian Indonesia, 2021)
Lontar is a plant that distributed in tropical areas and has beneficial values for the people in Tuamese Village, Biboki Anleu District, North Central Timor Regency. However, the information about the ethnobotany of lontar is not documented. This research aimed to determine the utilization of lontar in Tuamese Village. Data were collected using semi-structured interview techniques and field observation. The ethnobotany data were analyzed to calculate cultural significance index value. The results showed that the people in Tuamese Village who generally work as lontar farmers use stem, leaves, flowers, and fruit as building and fence materials, handicraft materials, food and drink ingredients, and firewood. Product from sap flower, namely liquid sugar, slab sugar, and traditional fermented drink (sopi) are the leading trade commodity. The utilization of lontar in Tuamese Village is grouped into seven forms of utilization with index of cultural significance 151 and classified very high. The classification means that lontar greatly affects people's lives in Tuamese Village and its use has become cultured. People's dependence on lontar is very high so the conservation effort needs to make the existence of lontar is maintained. Keywords: index cultural significance, lontar, Tuamese